Relationships between apparent cortical thickness and working memory across the lifespan - Effects of genetics and socioeconomic status - Krogsrud, Stine K.; Mowinckel, Athanasia M.; Sederevicius, Donatas; Vidal-Piñeiro, Didac; Amlien, Inge K.; Wang, Yunpeng; Sørensen, Øystein; Walhovd, Kristine B.; Fjell, Anders M. (Developmental cognitive neuroscience, 2021)
•Sub-components of working memory (WM) showed different lifespan trajectories.•WM capacity was related to apparent thinner cortex during childhood.•The WM-thickness effect could not be accounted for by general cognitive abilities.•The WM-thickness relationship was not mediated by genetics or socioeconomic status. Working memory (WM) supports several higher-level cognitive abilities, yet we know less about factors associated with development and decline in WM compared to other cognitive processes. Here, we investigated lifespan changes in WM capacity and their structural brain correlates, using a longitudinal sample including 2358 magnetic resonance imaging (MRI) scans and WM scores from 1656 participants (4.4–86.4 years, mean follow-up interval 4.3 years). 8764 participants (9.0–10.9 years) with MRI, WM scores and genetic information from the Adolescent Brain Cognitive Development study were used for follow-up analyses. Results showed that both the information manipulation component and the storage component of WM improved during childhood and adolescence, but the age-decline could be fully explained by reductions in passive storage capacity alone. Greater WM function in development was related to apparent thinner cortex in both samples, also when general cognitive function was accounted for. The same WM-apparent thickness relationship was found for young adults. The WM-thickness relationships could not be explained by SNP-based co-heritability or by socioeconomic status. A larger sample with genetic information may be necessary to disentangle the true gene-environment effects. In conclusion, WM capacity changes greatly through life and has anatomically extended rather than function-specific structural cortical correlates.